AN ANALYSIS OF POLITENESS AND MAXIM VIOLATED IN “BLADE RUNNER 2049” FILM - Anas Tmasia Yunita Serly; Supeno Supeno (INFERENCE: Journal of English Language Teaching, 2018)
Politeness strategy is a strategy that is done by someone to make his speech more politely. The politeness strategy can be found in daily conversation, a speech, debating events or from literary works, for instance films or novels. One of the literary works of concerning for this study is “Blade Runner 20489” film. The purpose of this paper is to describe the politeness strategies used in the film which can be found in the conversation between the characters. This research uses the theory of politeness strategy proposed by Lakoff (1973) and the theory of Maxim which proposed by Grice (1975). Lakoff classifies politeness strategies into three types: don’t impose, give options and be friendly. While, Grice proposed the theory of maxim into four types namely, maxim of quantity, maxim of quality, maxim of manner and maxim of relevance. The finding of this study indicates that the characters in Blade Runner 2049 employed all types of politeness strategies in relation to the maxim. It can be concluded that the used of politeness strategies in relation to the maxim can be found in this film.